Experimental Mycobacterium tuberculosis infection in the Chinese tree shrew. Issue 1 (13th October 2014) - Zhan, Lingjun; Ding, Hairong; Lin, Shuzhu; Tang, Jun; Deng, Wei; Xu, Yanfeng; Xu, Yuhuan; Qin, Chuan
Abstract In recent years, the Chinese tree shrew has been considered to be a promising experimental animal for numerous diseases. Yet the susceptibility of Mycobacterium tuberculosis (MTB) in Chinese tree shrew is still unknown. We infected Chinese tree shrews with a high dose (2.5 × 106 CFU) or a low dose (2.5 × 103 CFU) of the H37Rv strain via the femoral vein to cause severe or mild disease. Disease severity was determined by clinical signs, pathologic changes and bacteria distribution in organs. Furthermore, among lung samples of the uninfected, mildly and seriously ill Chinese tree shrews, differentially expressed protein profiles were analyzed through iTRAQ and validated by qPCR. Tuberculous nodules, skin ulceration, pleural effusion and cerebellum necrosis could be observed in seriously ill animals. Regulation of the actin cytoskeleton was newly defined as a possible MTB‐related pathway correlated with disease progression. This comprehensive analysis of the experimental infection and the depiction of the proteomics profiles in the Chinese tree shrew provide a foundation for the establishment of a new animal model of tuberculosis and provide a better understanding of the mechanism of tuberculosis.